KESENJANGAN STANDARISASI PROSES PENDIDIKAN DAN MUTU HASIL PENDIDIKAN - admin admin; Nur Hidajati (DIDAKTIKA, 2013)
Education as a system is composed of human endeavor as a concept that can be justified to give birth to a generation capable of preserving human values and high moral standing. Demands of the changing times have altered the global nature of human behavior became ucontrollable. As a manifestation of the government's responsibility it is necessary to national education standards as a means of control and controlling the dynamics of the education system with all its consequences. Through a process of national education standards of learning system constructed should be in line with the national objective in order to cultivate human values, forming awareness about the importance of civilized behavior that reflects human dignity.